Natural Descriptions in Thomson and in Donelaitis - Kuosaitė, Elena (Literatūra, 1973)
The link between Thomson’s poem "The Seasons" and Donelaitis’ "The Seasons" ("Metai") consists in their representing nature according to the four seasons of the year. Human life is connected with the cyclic motion of nature in both poems. But the interpretation of natural phenomena and man’s attitude towards them is different. Nature is the main object of description in Thomson’s poem. The poet carefully observes different phenomena of nature and tries to reveal their variety and multiplicity. Some of the descriptions are based not on direct observation of nature but on the information drawn from geographical literature (the tropical and the arctic landscape). Natural descriptions are also linked with the scientific investigations of his time. The hero of the poem is an educated man who is given to observation and meditation. The main object of description in Donelaitis’ poem is rather the life of peasants, the boors, than nature as such. Nature is presented here as an organic part of the boor’s everyday life. The poet observes it through the mind and eye of the common man. Thomson’s landscape is more diverse than Donelaitis’. It comprises more phenomena of nature with their different shades. It is also very poetic and refined, since the poet pays primary attention to the picturesque and harmonious in nature. Landscape in Donelaitis’ poem is quite commonplace, even the unattractive sides of nature are sometimes described, e.g., mud in autumn, different insects in spring, etc. But his landscape is very rich, full of expression and dynamics. The moral and philosophical interpretation of nature in Thomson is closely linked with the philosophical ideas of the eighteenth century, especially with the theory of universal order and harmony. Donelaitis’ poem, too, reflects the concepts of the eighteenth century but here it is the peasant’s perception of nature and man’s attitude to it that stands in the foreground. Because of their philosophic implications, the poems of Thomson and Donelaitis are not merely poems of natural descriptions or records of rural life. But, on the other hand, they differ from each other by their concept of man and universe, and by their aesthetic qualities.